Long-Term Follow-Up and Impact of Comorbidity before Allogeneic Hematopoietic Stem Cell Transplantation in Patients with Relapsed or Refractory Acute Myeloid Leukemia-Lessons Learned from the Prospective BRIDGE Trial - Middeke, Jan Moritz; Herbst, Regina; Parmentier, Stefani; Bug, Gesine; Hänel, Mathias; Stuhler, Gernot; Schäfer-Eckart, Kerstin; Rösler, Wolf; Klein, Stefan; Bethge, Wolfgang; Bitz, Ulrich; Büttner, Bozena; et al. (Biology of Blood and Marrow Transplantation, 2017)
In patients with relapsed or refractory (r/r) acute myeloid leukemia (AML), allogeneic hematopoietic stem cell transplantation (HSCT) is considered to be the only treatment providing long-term disease control. The BRIDGE trial studied the safety and efficacy of a clofarabine-based salvage therapy before HSCT in patients with r/r AML. Here, we report the long-term follow-up of this phase II multicenter trial and exploratory analyses on the impact of comorbidity on outcome. Eighty-four patients with a median age of 61 years (range, 40 to 75) were enrolled. Patients were scheduled for at least 1 cycle of salvage therapy with CLARA (clofarabine 30 mg/m(2); cytarabine 1 g/m(2), days 1 to 5). Chemo-responsive patients with a donor received HSCT after first CLARA. The conditioning regimen consisted of clofarabine 30 mg/m(2), day -6 to -3, and melphalan 140 mg/m(2) day -2. The Eastern Cooperative Oncology Group (ECOG) score, the hematopoietic cell transplantation-specific comorbidity index (HCT-CI), and the Cumulative Illness Rating Scale were obtained at study enrollment as well as before HSCT. Sixty-seven percent of the patients received HSCT within the trial. After a median follow up of 40 months, the estimated 3-year overall survival (OS) for all enrolled patients and those with HSCT within the trial was 40% and 55%, respectively. Relapse-free survival for patients who underwent transplantation with a complete remission afterwards (n = 50) was 48%, calculated from the day of transplantation. In multivariate analysis, both the HCT-CI and ECOG score had a statistically significant impact on OS with a hazard ratio of 1.22 (P = .025)and 1.72 (P = .001), respectively. Using a clofarabine-based salvage therapy combined with early allogeneic HSCT, we were able to achieve good long-term results for patients with r/r AML. In this cohort, both the HCT-CI and the ECOG scores gave prognostic information on OS, showing the feasibility and clinical relevance of comorbidity evaluation at the time of diagnosis of r/r AML patients.
EVALuna2:25768